PG95 Creation of a remote consultations virtual simulation course involving simulated patients for trainees who had been shielding during covid-19. (10th November 2020) - Bagg, Danielle; Finneran, Nicola; Hamilton, Carrie; Booth, Jane
Abstract : Background: Healthcare has changed dramatically in the past few months with changes in practice and an increase in remote consultations. 1 Many doctors have been shielding during the covid-19 pandemic and are now starting to return to work. This has caused anxiety, and a feeling of being under-prepared to return to practice. 2 Our objective was to support trainees of all specialties returning to work and teach them how to conduct virtual consultations. Summary of Work: A one day course was created to provide a background of how to conduct remote consultations as well as experience of conducting simulated consultations, including breaking bad news, initial clinic consultation, follow up review and addressing a patient concern. All involved were able to take part in this session from a location of their choice. Each participant had scenarios tailored to their specialty and was paired with a simulated patient (SP) to individually conduct consultations, using a mixture of telephone calls and video calls. As well as a group debrief via Zoom, participants received personalised written feedback from their SP for one of their scenarios. Summary of Results: A total of 12 trainees have attended the day to date, from specialties including internal medicine, acute medicine, psychiatry, paediatrics and general practice. Participants felt that their scenarios adequately catered to their specialty and their confidence in both returning to work and conducting remote consultations increased. The SPs were identified as a highlight of the course, giving the encounters realism and their written feedback can be used as evidence of patient interactions in their portfolios, highlighting areas for further development. Discussion, Conclusions and Recommendations: This course is innovative in delivering socially distant simulation involving SPs that can be undertaken whilst shielding or self-isolating. Finding new ways of conducting simulation is important, especially for doctors that are at higher risk from covid-19. Collaborating with SPs allows greater patient involvement as they directly feedback to participants and ensure that patient perspectives are heard. Ultimately, this patient centred approach is likely to improve care. The course has enabled trainees to become more confident in returning to work and conducting remote consultations. There is scope to widen participation to clinicians in all specialties that conduct remote consultations, as this is a skill that is not currently widely taught and requires enhanced communication skills. This course will become part of the regional Internal Medicine Training as well as local multi-specialty training. References: Rimmer, A., ( 2020) 'Covid-19: Shielding doctors express concerns about returning to work', BMJ, 370:m2918. General Medical Council, ( 2020) Remote Consultations, Available at: https://www.gmc-uk.org/ethical-guidance/ethical-hub/remote-consultations (Accessed 29/8/2020).